DIVERSITY OF INSECTS IN SAL (SHOREA ROBUSTA) FOREST AT SELAQUI REGION, DEHRADUN (INDIA) - DR. DINESH KUMAR BHARDWAJ,; KUMARI NEETU THAKUR, (International Journal of Pharma and Bio Sciences, 2015)
The study area is the “Selaqui” region of district Dehradun of the state of Uttarakhand in India. Dehradun is the capital of Uttarakhand and situated at the height in the foothills of 2073mm. It is located about 19 kms West-Northwest of capital city of Dehradun. Selaqui village is located at latitude 30.35’ and longitude 77.94’. The area has forest land which is rich in the Shorea robusta trees. The insects were collected, pinned, spreading, dried and preserved. Total 30 insects species belonging to different orders viz. Lepidoptera, Hymenoptera, Orthoptera, Coleoptera, Isoptera Odanata, was identified during the study period i.e April-May 2014. Among all orders Coeleoptera was dominated with 7 species with 36 no. of individuals. Lepidoptera was recorded with 6 species followed by Hemiptera with 5 species. Hymenoptera and Orthoptera with 4 species each. Diptera and Odonata with 2 and Dictyoptera and Isoptera with 1 species each. The diversity index was calculated by Shannon- Weiner Expression. In the present study, species diversity has been calculated, which is 1.380. This value shows high species diversity in the Sal forest.